The intellectual endeavour of Imam al-Shafi'i: aspects of his life and work - Muhamad Shukri, Abdul Salam (2005)
Al-Imam al-Shafi'i (150-204/767-820) was known as the founder of the Shafi'i school of law (madhhab). Al-Shafi'i was a man whose background amply fitted him for the role he was to play in Islamic scholarship. This article will briefly highlight aspects of al-Shafi'i's intellectual life in order to provide the background for a clear understanding of his contribution.